The Effectiveness of an Educational Intervention on Countering Disinformation Moderated by Intellectual Humility - Eduard-Claudiu Gross; Delia Cristina Balaban (Media and Communication)
There is an ongoing debate among scholars on how to tackle disinformation. Media education initiatives to increase literacy are effective ways to counter disinformation. Hence, the European Commission (2022) published Guidelines for Teachers and Educators on Tackling Disinformation and Promoting Digital Literacy Through Education and Training. The present research looked at the role of social media literacy in increasing awareness of the role of social media in spreading disinformation. We developed an educational intervention based on the European Commission guidelines. We investigated its impact on perceived social media literacy, the intention to share fake news on social media, and general conspiracy beliefs. We conducted a within-subject (two times measurement: before the educational intervention and one week after) +1 experiment with N = 127 young adults (aged 18 to 23). After filling in an initial survey, the experimental group received a 15-minute educational intervention on the role of social media for disinformation dissemination in complex digital information environments. One week later, all participants completed the second survey to assess perceived social media literacy and general conspiracy beliefs. In both surveys, participants saw three Instagram posts from a fictitious media outlet to express potential intentions to share on social media. Among the three posts, two showed false information. Findings showed that educational intervention produces a significant increase in perceived social media literacy and a decrease in general conspiracy beliefs. Intellectual humility moderates the impact of educational intervention on algorithmic awareness.